2020
DOI: 10.22495/cocv17i3art5
|View full text |Cite
|
Sign up to set email alerts
|

Women on bank boards and risk-taking: A cross-countries analysis on the moderating role of masculinity

Abstract: This study examines the effects of board gender diversity on a bank’s risk by applying a moderate multiple regression analysis on a dataset covering the years 2008-2017 and comprising 110 banks from Germany, Italy, Spain, and Switzerland. Masculinity, a country-level cultural dimension incorporating the behavioural expectations surrounding men and women in a society, is used as a moderator. Results suggest that high country-level masculinity stresses the risk-aversion of a bank’s women directors, therefore com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…In this case, many governance factors were considered, and the results show that some governance profiles, such as the presence of committees or women on the board of directors, are significant with respect to the performance of banks. Gallucci et al (2020) demonstrated the existence of a link between women on the board and banks' risk taking, arguing that the moderating role of masculinity at the country level negatively influences board diversity and intensifies women's risk aversion. From various reports (Owen & Temesvary, 2018;Strøm et al, 2014), it is possible to understand that women could reach top positions in a shorter time frame, improving the workplace environment and consequently the company performance (García-Meca et al, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, many governance factors were considered, and the results show that some governance profiles, such as the presence of committees or women on the board of directors, are significant with respect to the performance of banks. Gallucci et al (2020) demonstrated the existence of a link between women on the board and banks' risk taking, arguing that the moderating role of masculinity at the country level negatively influences board diversity and intensifies women's risk aversion. From various reports (Owen & Temesvary, 2018;Strøm et al, 2014), it is possible to understand that women could reach top positions in a shorter time frame, improving the workplace environment and consequently the company performance (García-Meca et al, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Indeed, previous studies have shown how larger board size improve the effectiveness of monitoring and control activities, with the possibility of better assessing risk management choices (Adams & Mehran, 2012; De Andrés & Vallelado, 2008). More recently, other authors have investigated the presence of a relationship between banks' performance and the multiple factors that characterize corporate governance (Gallucci et al, 2020; Grove et al, 2011; Selvam et al, 2006). Corporate governance scholars have pointed out the need to expand the presence of women in the top and middle management of companies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, appointing female directors can improve oversight and lessen the opportunistic conduct of managers. They think their female directors are better at monitoring because of this, and board gender diversity enhances managerial accountability, including CEO accountability and board meeting participation (Gallucci et al, 2020).…”
Section: Theoretical Reviewmentioning
confidence: 99%